Prospects of approach and characterization of Mar del Plata peri-urban, Argentina - Ferraro, Rosana (2013)
In Latin America in general, and in Argentina in particular, city growth without prior planning results in the formation of highly complex peri-urban areas. The urban-rural analysis based on the traditional model of country-city dichotomy is not enough to explain the processes that occur in these cities. On the basis of prior studies conducted in the peri- urban of Mar del Plata, Argentina, this paper aims to : a) characterize the peri-urban by studying its functions throughout history, b) propose a rereading for its further analysis through the complex systems theoretical-methodological approach, and c) describe the main areas that account for its special heterogeneity and complexity. From an integral viewpoint, and taking the physical, sociocultural, productive, urban- residential and digester subsystems into account, the analysis of the peri-urban allowed to define areas with differential characteristics. Such areas admit higher disintegration in more detailed scales, making it easy to understand their operation and their problems. In conclusion, the complex systems approach results appropriate to promote the development of management strategies in areas as heterogeneous as the peri-urban.